Increasing Rural Health Clinic Utilization with SMS Updates: Evidence from a Randomized Evaluation in Uganda - Luke E. Chicoine; Juan Carlos Guzman (Institute for the Study of Labor (IZA), 2016)
This paper examines an alternative to monitoring staff at a public health clinic in rural Uganda. The program sent SMS updates regarding confirmed attendance of clinic staff and activities to randomly selected cell phone-owning households in the local community. A difference-in-difference approach is used to evaluate the impact of the SMS program, and finds the messages led to an increase in clinic attendance, the receipt of medicine, and reduced duration of illness for young children aged six and under. However, these benefits are only seen for children who are the same sex as the cell phone owner, suggesting favoritism towards the health of these children. These benefits are found to be similar for both boys and girls.
Keywords: I15; J13; O22; 330; mobile technology; parental favoritism; children's healthcare; Uganda